INTERNATIONAL AND NATIONAL IN ACADEMIC PAPER - M. N. Mileyeva (Moscow Polytechnic University, 2018)
The author considers the significance of teaching post-graduate students the module of written scientific communication to avoid problems facing them in future publishing career. The notion 'academic writing' is interpreted as the key to realizing national differences in intercultural written interaction. The author highlights the inevitable interference of the English scientific language and the native language of a researcher, the international part of a modern academic paper being English as lingua franca. Typology of cultures helps to explain possible misunderstanding in reading academic papers. Linguistico-culturological analysis of several scientific articles written in English by investigators from various countries allows the author to conclude that any researcher writes in English under unconscious domination of his national features.